L’enseignement de l’histoire et la conscience citoyenne des élèves au Québec - Marc-André Éthier; Jean-François Cardin; Jean-Pierre Charland (Revue LISA)
This article describes Quebec’s history curriculum in a context of renewed interest over pluralism. It also discloses the preliminary results of a research project concerning the links that exist between history teaching (seen equally as an official narration and as a pool of research techniques) and conceptions expressed by young Québécois, both native and immigrant, relating to history and citizenship.The article is two-fold. The first part explains the educational context in which this project evolves, including the ministerial position regarding to cultural heterogeneity. The second part summarizes the project itself and its results.